Determinants of growth in HIV‐exposed and HIV‐uninfected infants in the Kabeho Study. Issue 3 (29th January 2019) - Lane, Charlotte E.; Bobrow, Emily A.; Ndatimana, Diuedonne; Ndayisaba, Gilles F.; Adair, Linda S.
Abstract: HIV‐exposed and HIV‐uninfected (HEU) infants may be at increased risk of poor health and growth outcomes. We characterized infant growth trajectories in a cohort of HEU infants to identify factors associated with healthy growth. HIV‐positive women participating in prevention of mother‐to‐child HIV transmission programmes in Kigali, Rwanda, were followed until their infants were 2 years old. Infant anthropometrics were regularly collected. Latent class analysis was used to categorize infant growth trajectories. Multiple logistic regression was used to estimate the odds of infants belonging to each growth trajectory class. On average, this population of HEU infants had moderate linear growth faltering, but only modest faltering in weight, resulting in mean weight‐for‐length z ‐score (WLZ) above the World Health Organization (WHO) median. Mean WLZ was 0.53, and mean length‐for‐age z ‐score (LAZ) was −1.14 over the first 2 years of life. We identified four unique WLZ trajectories and seven trajectories in LAZ. Low neonatal weight‐for‐age and a high rate of illness increased the likelihood that infants were in the lightest WLZ class. Shorter mothers were more likely to have infants with linear growth faltering. Female infants who were older at the end of exclusive breastfeeding were more likely to be in the second tallest LAZ class. In conclusion, the current WHO recommendations of Option B+ and extended breastfeeding may induce higher WLZ and lower LAZ early in infancy. However, there is considerable heterogeneity in growth patterns that is obscured by simply analysing average growth trends, necessitating the analysis of growth in subpopulations.